(De)Colonizing Pedagogy: Possibilities and Tensions in Undergraduate Transformative Learning Through Simulation. (April 2023) - Carrick-Hagenbarth, Jessica; Maton, Rhiannon M.
This article employs transformative learning and decolonial theories to investigate the efficacy of simulation pedagogy for undergraduate student learning about refugees and the internally displaced. The simulation of refugee experience was adapted from the Doctors Without Borders' Forced From Home exhibit and facilitated by an experienced affiliate for eighty-nine education and economics undergraduate students. Data include surveys, debriefing discussions, and written reflections. We ask: Does simulation pedagogy support transformative learning toward the decolonial goals of recognizing and deconstructing current power relations? How or how not? Overall, we find that simulation pedagogy successfully supports initial stages of transformative learning through engaging a combination of kinesthetic (body), affective (heart), and cognitive (mind) realms to shift students' perspectives and knowledge. Through a decolonial lens, we chronicle the strengths and limitations of transformative learning processes and find that the simulation pedagogy achieved a combination of colonial and decolonial purposes.